Հեռուստատեսության դիտման նախընտրությունները և ազդեցությունը Իրանի երիտասարդության արժեքային կողմնորոշումների վրա - Մահմուդ Խալիլի (Զանգակ հրատ.)
В статье представлено исследование предпочтений иранской молодежи при телепросмотре, в частности, выбор между доступными в Иране телеканалами, и формирование ценностной ориентации в связи с предпочитаемыми телеканалами и телепередачами. В частности, рассматриваются предпочтения молодежи при просмотре западных и иранских телепередач, причины, по которым делается соответствующий выбор, и как влияют данные предпочтения на их образ жизни. The study on television consumption by Iranian youth is represented in the article. The study demonstrates the ways in which the choice of TV channels and programs determine socialization process, value orientation among young people, including preferences to watch Iranian and pro–Western programs, learning from them, getting oriented about either stay or emigration to the countries where the more likely life is shown, possible conflicts with older generation, etc.
Keywords: Գիտնականի մտորումներ; Սոցիոլոգիա